The influences of asset turn over and net working capital to the return on investment (Survey on state employee cooperatives (KPRI) in Bandung city) - Sjaiful R.L.; Saudi M.H.M.; Saud H.F.M. (Institute of Advanced Scientific Research, Inc., 2024)
Cooperative is the cutting edge in managing public funds. Besides collecting public funds are also channeled funds to the needy. Cooperative into an alternative community in saving and lending money because it is simpler and less complicated than banking institutions. Although the form of cooperatives, fund management institutions still have to manage the assets properly. One of them is to manage the turnover of assets in order to obtain optimal results. The return on investment (ROI) illustrates the company's ability to generate profits by using total assets (wealth) which belongs to the company. This study aims to determine the effect of the asset turnover rate of return on investment (ROI). The method used in this research is explanatory research methods. The population used in this study are all KPRI registered and submit financial statements in 2014 to the Department of Cooperatives, Industry and Trade of Bandung in 2015. The sampling technique used purposive sampling and analysis used is multiple regression and processed using SPSS 21,The results showed that the turnover of assets not significantly influence and net working capital significantly influence on the return on investment.